STUDY OF ADDITIONAL FIN TO INCREASE EFFICIENCY OF SUPERHEATER AT HEAT RECOVERY STEAM GENERATOR - Bramantya, Muhammad Agung (Jurnal Rekayasa Mesin, 2024)
Power plants are part of industrial facilities used to produce and generate electricity from various power sources; one of those is PLTGU (Pembangkit Listrik Tenaga Gas dan Uap or Gas and Steam Power Plant). PLTGU is a combined cycle between PLTG and PLTU. It is necessary to achieve a high-capacity target for the PLTGU to increase the generator's efficiency. One way to increase the efficiency of gas and steam power plants is by optimizing heat transfer in the Heat Recovery Steam Generator (HRSG). HRSG has several modules such as superheater, evaporator, economizer, and preheater. One that plays an essential role in absorbed high-temperature steam from the gas turbine is the superheater. The function of the superheater is to utilize the heat from the flue gas to reheat the fluid needed for the steam turbine. In this research, improvements of superheater were made with several fin variations at HRSG PLTGU. Variable of superheater refer to data on the layout of the HRSG PLTGU. Autodesk Inventor is used to modeling flue gas domain, tube, and fin. Additional of the fin has the purpose of optimizing heat transfer distribution in steam through a tube, such as an outlet temperature and efficiency of steam in tube superheater. The use of CFD (Computational Fluid Dynamic) with ANSYS Fluent could use to determine the temperature distribution of the superheater. The most optimal efficiency and outlet temperature of variation fin is the annular fin variation compared to the rectangular and straight fin variations.